A Century of Global Equity Market Correlations - Quinn, Dennis P; Voth, Hans-Joachim (American Economic Review, 2008)
In this paper, we use a unique long-run dataset of regulatory constraints on capital account openness to explain stock market correlations. Since stock returns themselves are highly volatile, any examination of what drives correlations needs to focus on long runs of data. This is particularly true since some of the short-term changes in co-movements appear to reverse themselves (Delroy Hunter 2005). We argue that changes in the co-movement of indices have not been random. Rather, they are mainly driven by greater freedom to move funds from one country to another. In related work, Geert Bekaert and Campbell Harvey (2000) show that equity correlations increase after liberalization of capital markets, using a number of case studies from emerging countries. We examine this pattern systematically for the last century, and find it to be most pronounced in the recent past. We compare the importance of capital account openness with one main alternative explanation, the growing synchronization of economic fundamentals. We conclude that greater openness has been the single most important cause of growing correlations during the last quarter of a century, though increasingly correlated economic fundamentals also matter. In the conclusion, we offer some thoughts on why the effects of greater openness appear to be so much stronger today than they were during the last era of globalization before 1914.(This abstract was borrowed from another version of this item.)